Nutrient flows and balances in intensive crop-dairy production systems in the Kenya highlands - Utiger, C.; Romney, Dannie L.; Njoroge, L.; Staal, Steven J.; Lukuyu, Ben A.; Chege, L. (International Livestock Research Institute, 2000)
Sustainability of their agricultural systems is essential for many tropical countries where the majority of the people depend upon agriculture for their livelihoods. In the short term economic sustainability is the main factor influencing viability of an agricultural system and of the farms which form its production units. In the long-term, however, economic viability will depend upon the nutrient status of a system. In common with much of the eastern African highlands, Kiambu district in central Kenya has high and increasing pressure on its land and farmers are responding by steadily intensifying their farming systems. This paper addresses the hypothesis that where ruminant livestock are present in intensifying smallholder cropping systems, they make a positive contribution to the nutrient status of the smallholder system. For 21 crop-dairy farms representative of the major smallholder-farming systems in the central highlands of Kenya, annual nutrient balances were determined in a longitudinal study. The farms were visited twice a week; data on all farm inputs and outputs were collected, based on farmer recall. Measures of livestock feed inputs were collected fortnightly. Estimates of nutrient gains and losses in the soil resulting from erosion, leaching, denitrification, volatilisation and N fixation were taken from the literature. Using these data, annual nutrient balances per hectare were estimated for N, P and K. The majority of the sample farms had balanced nutrient flows or were in positive balance for N, P and K overall because of positive flows to the dairy sub-unit, which counterbalanced the outflows from the crop sub-unit. The dairy unit contributed significantly, principally through feed purchases, particularly concentrates for lactating cows. Napier grass and crop residues were also purchased, and large quantities of roadside grass were collected from outside the farms. On the majority of the farms the nutrients returned to the cropping land as manure (which consisted of faeces, bedding material and feed refusals) contributed more nutrients than inorganic fertilisers. It is concluded that the dairy cattle played a major role in contributing nutrient in-flows into these intensive smallholder farms, as well as providing the household’s regular source of income through milk sales.